دراسة تحليلية عن كتاب النحو الواضح في قواعد اللغة العربية لعلي الجارم والمصطفى آمين الجزء الأول إلى الثالث للمرحلة الابتدائية من ناحية منهج تأليف الكتاب والمزايا والعيوب - Asia, Nur (Cahaya Ilmu Bangsa Institute, 2025)
Research to Analytical study of the book Nahwu wadhih fii qawaaidi al-lughah al arabiyah by Ali Jaarim and Musthafa Amin, volumes 1-3 for beginners in terms of book compilation methods, and advantages and disadvantages. This research focuses on the problem of the method of compiling the book An-Nahwu Al-Wadhih along with the advantages and disadvantages contained in the book. The formulation of the problem of this research is; what method is used by the author in compiling the book An-Nahwu Al-Wadhih, what are the advantages and disadvantages of this book. The purpose of this study is as follows; to find out the method of compiling An-Nahwu Al-Wadhih, to find out the advantages and disadvantages of this book. The method used in this study is a qualitative research method that uses a qualitative approach, with the type of library research, with a book review analysis method. The results that can be obtained based on this analysis are that the method of compiling the book An-Nahwu Al-Wadhih uses the Al-Istinbatiyah or inductive method, namely where the author of the book starts explaining the material from examples to rules or from specific to general, and there are several advantages and disadvantages in this book.